Incidence of Positive Severe Acute Respiratory Syndrome Coronavirus Polymerase Chain Reaction After Coronavirus Disease 2019 Vaccination With up to 8 Months of Follow-up: Real-life Data From the Capital Region of Denmark. (7th January 2022) - Heftdal, Line Dam; Schultz, Martin; Lange, Theis; Knudsen, Andreas Dehlbæk; Fogh, Kamille; Hasselbalch, Rasmus Bo; Linander, Christine Borgen; Kallemose, Thomas; Bundgaard, Henning; Grønbæk, Kirsten; Valentiner-Branth, Palle; Iversen, Kasper; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) vaccines are implemented worldwide in efforts to curb the pandemic. This study investigates the risk of a positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reverse transcriptase polymerase chain reaction (RT-PCR) test following BNT162b2 vaccination in a large real-life population in Denmark. Methods: Vaccination status and positive SARS-CoV-2 RT-PCR results from adults in the Capital Region of Denmark (n = 1 549 488) were obtained from national registries. PCR testing was free and widely available. The number of positive PCR tests per individual at risk was calculated as weekly rates. Time to positive PCR test was modelled using Kaplan-Meier methods and hazard ratios (HRs) were calculated using Cox regression. Results: A total of 1 119 574 individuals received the first dose of BNT162b2 and 1 088 879 received a second dose of BNT162b2. Individuals were followed up to 8.7 months after first dose (median: 5.5 months; interquartile ratio: 4.1–8.7). Rates of PCR-confirmed SARS-CoV-2 infection 2–4 months after the second dose were 0.21, 0.33, and 0.36 per 1000 individuals per week at risk for July, August, and September, respectively. Four or more months after the second dose, the rates were 0.56, 0.76, and 0.53 per 1000 individuals per week at risk for July, August, and September, respectively. HR of SARS-CoV-2 infection after the second dose was 0.2 (95% confidence interval, .05–.48; P = .001) for individuals with 8 months' follow-up. Conclusions: Individuals who received 2 doses of the BNT162b2 COVID-19 vaccine had a low risk of breakthrough infection after up to 8 months of follow-up. However, there was a tendency toward higher rates with longer follow-up. Abstract : In this study of 1 549 488 individuals in the Capital Region of Denmark, of which 1 119 574 were vaccinated against SARS-CoV-2, we found that individuals who received 2 doses of a COVID-19 vaccine had very low risk of breakthrough infections with SARS-CoV-2.